Identification of Elder Abuse at Emergency Departments: What Competencies are Required from Staff? - Salminen-Tuomaala, Mari; Tiainen, Juha; Paavilainen, Eija (European Journal of Applied Sciences, 2024)
The purpose of this mixed method study was to describe emergency department nursing staff’s ratings and experiences of their competencies in identifying elder abuse. The target group consisted of nursing staff in emergency departments of one university hospital and four central hospitals in Finland. The staff were Registered Nurses, Paramedic Nurses and Practical Nurses. The study is part of a larger research project on the identification of abuse, carried out with staff in prehospital and emergency department care. The data was collected using an electronic Webropol survey in autumn 2022 and spring-summer 2023. The quantitative data was analyzed using IBM Statistics for Windows 28 and the qualitative data using inductive content analysis. In the experience of emergency department nursing staff, it was easier to identify physical abuse, compared to psychological or social abuse or neglect of care in their older patients. The staff were well aware of risk factors associated with elder abuse, but their detection was not easy in short care contexts. According to the study results, elder abuse identification competencies in emergency departments include detection of the signs of abuse; assessment of the seriousness of the situation; interaction skills; emotional intelligence and situational awareness, and ethical competencies. In addition, the results highlight the importance of multiprofessional expertise in ensuring the patient’s safe follow-up care and coping at home. The identification of elder abuse is challenging in emergency departments and requires the development of multiple competencies and knowledge, especially regarding the detection of the signs of abuse, assessing the seriousness of the situation and interaction skills.